Ultrasound-guided tru-cut biopsy in the management of advanced abdomino-pelvic tumors - Fischerova, D; Cibula, D; Dundr, P; Zikan, M; Calda, P; Freitag, P; Slama, J (International journal of gynecological cancer, 2008)
The goal of this study was to evaluate the accuracy and safety of ultrasound-guided tru-cut biopsy in patients with either primarily inoperable pelvic tumor, advanced tumor and compromised performance status, or recurrent pelvic tumor. Altogether, 90 patients were enrolled and only 4 were not suitable for tru-cut biopsy. The biopsy was taken either from pelvic tumor (54.6%), peritoneal visceral or parietal metastases (31.4%), or omental cake (14%). Samples were obtained transvaginally (53.5%) or transabdominally (46.5%). A diagnosis consistent with primary ovarian malignancy was made in 62.8%, metastatic ovarian involvement was found in 10.5%, and extraovarian tumor in 26.7%. The obtained tissue was adequate for histologic diagnosis in 80 out of 86 cases. In four cases, repeated biopsy was required to obtain a sufficient tissue sample. False-negative samples without tumor tissue were obtained in two cases, and those patients were referred for either laparoscopy or minilaparotomy. The diagnostic accuracy of ultrasound-guided tru-cut biopsy reached 97.7% (95% CI 91.85-99.72%). There was only one complication, a bleeding from tumor in a patient with mild thrombocytopenia, requiring laparotomy. In conclusion, ultrasound-guided tru-cut biopsy is safe, reliable, and cost-effective diagnostic method. It can be performed in an outpatient setting without the need for general anesthesia and provides an adequate specimen for histologic analysis, including immunohistochemical methods. It should, therefore, be considered as a method of choice for histologic verification of both advanced primary and recurrent abdomino-pelvic tumors.
Keywords: Minimally Invasive Surgical Procedures; Postoperative Complications; chirurgie s pomocí počítače; progrese nemoci; Abdominal Neoplasms; Ultrasonography, Interventional; Neoplasm Staging; Adult; biopsie; Aged; dospělí; Surgery, Computer-Assisted; senioři; pooperační komplikace; Disease Progression; algoritmy; intervenční ultrasonografie; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; Algorithms; nádory břicha; Biopsy; Pelvic Neoplasms; miniinvazivní chirurgické výkony; nádory pánve; Female; studie proveditelnosti; lidé středního věku; staging nádorů; Middle Aged; Feasibility Studies